Supporting law students in the transition to higher education: an intervention - Bainbridge, Ian (2023)
The transition from further education to higher education is a process that can involve a number of significant and interconnected challenges and barriers for students from a variety of backgrounds to overcome. Not knowing what to expect, being uncertain as to what is expected of them and trying to ‘fit-in’ and develop a sense of belonging are challenges that all students will face to varying degrees. Becoming integrated into an academic and supportive environment can provide a positive foundation to support this transition.